2015
DOI: 10.1111/jgh.13030
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution and characteristics of genotype A hepatitis B virus infection in acute and chronic hepatitis B patients in Japan

Abstract: The distribution of HBV genotypes is quite different between AHB and CHB in Japanese patients. Genotype A infection is spreading in young adults of Japanese CHB patients. Sequences derived from Japanese AHB patients were identical to or closely resembled the sequences derived from other Japanese AHB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 36 publications
(66 reference statements)
1
39
2
1
Order By: Relevance
“…speculated in their review that HBV subgenotypes A2 and C are likely to predominate in populations at high risk of infection via sexual transmission 57. Additionally, HBV genotype A develops into a persistent infection more often than genotype C 5859.…”
Section: Epidemiology: Incidence and Prevalencementioning
confidence: 99%
“…speculated in their review that HBV subgenotypes A2 and C are likely to predominate in populations at high risk of infection via sexual transmission 57. Additionally, HBV genotype A develops into a persistent infection more often than genotype C 5859.…”
Section: Epidemiology: Incidence and Prevalencementioning
confidence: 99%
“…In Japan, an estimated 1.1‐1.4 million individuals (about 1% of the country's population) are infected with HBV; most of these infections were caused by mother‐to‐child transmission before the start of a nationwide HB immunization program initiated by the Japanese government in 1986. About 80% of the HBV‐infected patients in mainland Japan were HBV genotype C . Genome‐wide association studies (GWASs) have identified several susceptibility loci with the risk of chronic hepatitis B (CHB) infection in Asian and Arabian populations, including HLA class II, EHMT2 , TCF19, FDX1 , HLA‐C , UBE2L3 , and VARS2‐SFTA2 .…”
mentioning
confidence: 99%
“…Ito et al also found that prevalence of genotype A in chronic hepatitis B accounts for 4.1% and that genotype A spreads among young adult Japanese patients with chronic hepatitis B . This prevalence was significantly higher than that of a prior nationwide study conducted between 2000 and 2001, in which Orito et al reported a 1.7% prevalence of genotype A in chronically infected patients .…”
mentioning
confidence: 89%